ISOLASI DAN SELEKSI RIZOBAKTERI YANG BERPOTENSI SEBAGAI AGEN PENGENDALI PANTOEA STEWARTII subsp. STEWARTII PENYEBAB LAYU STEWART PADA TANAMAN JAGUNG - Rahma, Haliatur; Zainal, Aprizal; ., Suryati (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2016)
Isolation and selection of rhizobacteria potentially as biocontrol agents against Pantoea stewartii subsp. stewartii causingÂ stewartâs wilt disease in maize. Group of bacteria that colonize plant roots were known as Plant Growth PromotingÂ Rhizobacteria (PGPR), in addition to capable of suppressing the development of pathogens also has the ability to improve plant health. This study aims to isolate rhizobacteria from rhizosphere of maize in West Sumatera. Rhizobacteria were characterized and tested for its ability to suppress the bacteria Pantoea stewartii subsp. stewartii causes stewart wiltâs disease on maize. In this research 15 isolates of rizobacteria potential as biological agent were found, i.e. 6 isolates of the fluorescens bacteria group, 5 isolates of non fluorescens bacteria group and 4 isolates of heat-resistant bacteria group.